2017
DOI: 10.1103/physrevb.95.064105
|View full text |Cite
|
Sign up to set email alerts
|

Reversible structural transition in nanoconfined ice

Abstract: The report on square ice sandwiched between two graphene layers by Algara-Silleret et al. [Nature 519, 443 (2015)] has generated a large interest in this system. Applying high lateral pressure on nanoconfined water we found that monolayer ice is transformed to bilayer ice when the two graphene layers are separated by H=6, 7Å. It was also found that three layers of a denser phase of ice with smaller lattice constant is formed if we start from bilayer ice and apply a lateral pressure of about 0.7 GPa with H=8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
(37 reference statements)
1
25
0
2
Order By: Relevance
“…2d found at low densities. Interestingly, the two monolayers of square ice are out-of-registry (AB stacking) and they are not connected by hydrogen bonds (HBs) 23 , 65 . This is rather unusual since most ices in bulk and confined water are characterized by a continuous hydrogen-bond network.…”
Section: Resultsmentioning
confidence: 99%
“…2d found at low densities. Interestingly, the two monolayers of square ice are out-of-registry (AB stacking) and they are not connected by hydrogen bonds (HBs) 23 , 65 . This is rather unusual since most ices in bulk and confined water are characterized by a continuous hydrogen-bond network.…”
Section: Resultsmentioning
confidence: 99%
“…Computer simulation techniques, like molecular dynamics (MD), can aide in the understanding of confined systems that are hard to investigate experimentally. MD has already been shown to be useful in understanding confined systems, however accurately modeling the phase behavior of unconfined water through MD simulations has already proved to be difficult due to its complex phase diagram . Under confinement, the combination of the limited translational and rotational degrees of freedom and water/surface interactions adds an extra challenge as they can both influence the properties of confined water.…”
Section: Introductionmentioning
confidence: 99%
“…8,28 Besides thermodynamic control parameters, such as pressure or temperature, the phase behavior of water under confinement is affected by the commensurability between the confinement distance and the density of water. 5,8,11,27,28 For example, driven through incommensurate transitions, a transformation from a liquid, to a low-density ice phase, back to a high-density liquid, to finally a high-density ice phase, has been predicted for water nanofilms. 9 In another recent study, it was found that oscillations in the shear viscosity of confined water of several orders of magnitude occur over small variations in the confinement distance (under 1 Å).…”
mentioning
confidence: 99%